(untitled) (BIS Humanities and Social Science, 2026)
The waste management challenges in the Special Region of Yogyakarta stem not only from the limited capacity of final disposal sites but also from the weak implementation of regulatory frameworks governing waste governance. These shortcomings have led to increased public complaints submitted to the Ombudsman of the Republic of Indonesia, Yogyakarta Regional Office, as a corrective mechanism against maladministration in public service delivery. This study examines the local government’s compliance with the Ombudsman’s recommendations in implementing waste management policies grounded in the principles of transparency, accountability, and the attainment of Sustainable Development Goal (SDG) 12 on responsible consumption and production. Employing a juridical-empirical approach, the research integrates normative analysis of relevant regulations and good governance principles with empirical observations of local government public communication practices regarding waste services and responses to citizen complaints. Preliminary findings indicate a persistent gap between regulatory mandates and practical implementation, driven by weak coordination, limited information disclosure, and low responsiveness to Ombudsman recommendations. The study highlights the urgency of strengthening the institutional force of Ombudsman recommendations through derivative regulations and improved waste processing infrastructure to advance more accountable and sustainable waste governance.